Argon glow discharge plasma‐reduced palladium nanoparticles supported on activated carbon for Suzuki and Heck coupling reactions. (1st August 2016) - Liu, Yang; Bai, Xuefeng
Abstract : Palladium nanoparticles supported onactivated carbon were prepared by argon glow discharge plasma reduction (Pd/C‐P) without any chemical reducing agents and protective agents. The as‐prepared Pd/C‐P catalyst was characterized using nitrogen adsorption–desorption, X‐ray diffraction and transmissionelectron microscopy analyses. The results showed that the palladium nanoparticles reduced by plasma are well dispersed with a smaller particle size than commercial Pd/C. Pd/C‐P exhibited a highcatalytic activity in Suzuki and Heckcoupling reactions . Moreover, there was no obvious loss ofcatalytic activity even after eight repeated cycles, showing good reactivity and recyclability. Abstract : Palladium nanoparticles supported on activated carbon (Pd/C‐P) were prepared by an argon glow discharge plasma reduction method. The Pd nanoparticles were well dispersed on the activated carbon and had a narrow distribution range with smaller particle size than commercial Pd/C. Pd/C‐P exhibited high catalytic activity for Suzuki and Heck coupling reactions. The Pd/C‐P catalyst can be reused eight times without an obvious reduction in catalytic activity.